(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Network narratives, hyperlink or ensemble movies are a seductive introduction to the complexity of our globalized world and our social interactions. Using two popular examples, Babel and Love Actually, I explore the uses and the limits of the social network, respectively through a global and deterritorialised network and a local one that reveals kinship. Using the dynamic of networks to represent the characters’ interactions, these types of films nonetheless need boundaries. In the context of globalization, hyperlink movies are the mirror of a new geography but cannot show the complexity and the extent of it all since they are restricted by their own limits, being a narrative medium with a specific length. Hyperlink movies therefore present an interesting compromise, using a popular narrative technique to showcase a complex phenomenon.